2021
DOI: 10.3389/fnut.2021.684588
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Lactobacillus plantarum HFY09 on Ethanol-Induced Liver Injury in Mice

Abstract: Lactobacillus plantarum is a bacterial strain that is used as a probiotic with health-promoting effects. Our study investigated the hepatoprotective effect of Lactobacillus plantarum HFY09 (LP-HFY09) in mice with ethanol-induced liver injury. The protection afforded by LP-HFY09 was evaluated by observing the morphology of hepatic tissue and measuring liver lipid indexes and function indexes, levels of anti-oxidative enzymes, and anti-inebriation enzymes, as well as oxidative metabolism-related gene expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Significant differences at P < 0.05 and P < 0.01 are denoted with + and *, respectively. elevated in the HF group and FRT4 intervention decreased the gene expression of TLR4 and IL-6, which is in line with the reports that IL-6 was diminished by the treatment with L. reuteri V3401 in adults with metabolic syndrome and L. plantarum HFY09 alleviated inflammation by decreasing the levels of pro-inflammatory factors IL-6, IL-1β, and TNF-α in ethanol-induced liver injury in mice (31,32). These results indicated that FRT4 intervention enhanced choline metabolism, suppressing inflammatory responses by decreasing the expression of pro-inflammatory biomediators.…”
Section: Discussionsupporting
confidence: 88%
“…Significant differences at P < 0.05 and P < 0.01 are denoted with + and *, respectively. elevated in the HF group and FRT4 intervention decreased the gene expression of TLR4 and IL-6, which is in line with the reports that IL-6 was diminished by the treatment with L. reuteri V3401 in adults with metabolic syndrome and L. plantarum HFY09 alleviated inflammation by decreasing the levels of pro-inflammatory factors IL-6, IL-1β, and TNF-α in ethanol-induced liver injury in mice (31,32). These results indicated that FRT4 intervention enhanced choline metabolism, suppressing inflammatory responses by decreasing the expression of pro-inflammatory biomediators.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, Cu/Zn-SOD, Mn-SOD, and CAT mRNA expressions in the three intervention groups were significantly higher than those in the model group. So far, the strains that have been proved to have antioxidant capacity include: Lactobacillus acidophilus, Lactobacillus sake, Bifidobacterium longum, Lactobacillus fermentum, etc (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…TCONS_00334653, one of the different lncRNA between prediabetic patients with HTG and NTG, which the target mRNA is HIST1H2BM, was corresponding to the pathways of Alcoholism, SLE and Viral carcinogenesis. Previous study has indicated that damage occurred to the lipid metabolic function in the animal models of ethanol-induced liver-injury, which was manifested by increased levels of TC and TG [ 25 ]. Moreover, alcohol emits toxicity when it is just ingested, and the alcohol metabolite acetaldehyde is highly toxic in the body, which can affect multiple organs and cause physiological effects, resulting in various metabolic diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%